Exploring Perspectives of the Student Competencies Needed to Advocate for Agriculture - Garrett M. Steede; Laura M. Gorham; Erica Irlbeck (Journal of Applied Communications, 2016)
The agricultural and natural resources industries are increasingly faced with remarks and skepticism from consumers and activists alike. Equipping those in industry as well as college graduates with skills to effectively share agriculture’s story through a variety of mediums continues to increase in importance. This qualitative study sought to explore learning objectives and curriculum goals that agricultural advocates have for an undergraduate agricultural advocacy course. Phone interviews with individuals involved in agricultural advocacy revealed two-way communication skills were important when communicating with the public. Active listening, communicating with an open mind, communicating at a level of understanding, and equipping oneself with an arsenal of industry knowledge and contacts were found to be key learning outcomes for a course such as this. Further, role-playing activities, professional experiences, and online media communication abilities were also found to be important class assignments, activities, and skills that would allow students to perfect these two-way communication skills. From the findings of this study, undergraduate educators may have a better understanding of the importance of incorporating two-way communications into their curriculum as well as have a guideline for developing a course for agricultural advocacy within their agricultural education, communications, and leadership programs. The findings of this study may also help communications practitioners and Extension personnel as they prepare for agricultural advocacy efforts within their organizations.
Keywords: Advocacy; Curriculum; Changing Public Perception; Two-way Symmetrical Model of Communication